The Effect of Digitalization of the Recruitment Process, Use of Data Analysis Tools, and Generational Diversity on Workforce Quality at Technology Start-up Companies in West Java - Apriyanto, Apriyanto; Rukmana, Arief Yanto; Bunyamin, Ilham Akbar (West Science Social and Humanities Studies, 2025)
This study examines the impact of three critical factors—Digitalization of the Recruitment Process, Generational Diversity, and Use of Data Analysis Tools—on Workforce Quality in technology start-up companies in West Java. Using a quantitative approach, data were collected from 150 respondents with a Likert scale (1-5) and analyzed using Structural Equation Modeling (SEM-PLS 3). The results indicate that all three factors positively influence workforce quality, with Generational Diversity having the most substantial effect. Specifically, the digitalization of recruitment processes enhances workforce quality by improving candidate selection, while data analysis tools contribute to informed decision-making in talent management. The findings highlight the importance of integrating digital technologies and fostering a diverse workforce to optimize workforce quality in start-up environments. The study provides actionable insights for practitioners seeking to improve workforce performance through technological and diversity initiatives.